IMPLEMENTATION OF THE HEALTH AND SAFETY OF STUDENTS IN THE SUBJECT BATIK TEXTILE CRAFT WORKSHOP PRODUCTION DESIGN STATE 8 SMK PADANG - Fitriani, Desi; Ernawati, Ernawati; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2016)
This study aims to describe the picture concerning, the implementation of occupational health and safety of students in the batik’s subjects in Production Design Textile Craft Workshop SMK Negeri 8 Padang terms of three indicators, namely (1) Application of K3 student self (2) Application of K3 in use equipment and materials (3) Application of K3 in the work environment. This research is descriptive quantitative research and the research data is numeric or statistical analysis. The population and the sample in this study are all students studying in class XI batik namely DPK Textiles SMKN 8 Padang amounted to 81 people. Data analysis in this research using descriptive analysis techniques percentage through the statistic program Solusion Product and Service (SPSS) version 16. Results of research on the application K3 class XI students on subjects DPK Textile Batik Workshop Textile DPK SMKN 8 Champaign high category (74.61%). It can be viewed in terms of the implementation of K3 students self-sufficient in the category (58.86%). In terms of the implementation of K3 students in the use of tools and materials that are in high category (79.62%). In terms of the implementation of K3 students in the work environment at the high category (79.73%). K3 conclusion of the results of the implementation of K3 on the batik’s subjects already applying K3 with excellent. It can be terms K3 application of the self, the use of tools and materials, and in the working environment with excellent batik to be maintained and further enhanced. It is expected the school to be able to apply on the K3 students on subjects followed the practice of batik.Kata Kunci: Kesehatan dan keselamatan kerja, Mata pelajaran batik